2022
DOI: 10.3389/fcimb.2022.935068
|View full text |Cite
|
Sign up to set email alerts
|

Genital Microbiota of Women From Six Ethnic Groups With and Without Human Papillomavirus Infection in Shangri-La, China

Abstract: BackgroundA diversity of microorganisms is associated with human health and exists in a state of dynamic equilibrium. This diversity has direct implications for the assessment of susceptibility to infectious diseases, especially human papillomavirus (HPV) infection.MethodsHere, we investigated the relationships between HPV infection and vaginal, cervical, and gut microbiota composition and assessed the levels of genital immune mediators. We selected a multiethnic area in Yunnan Province, China, to collect samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…In this study, we have found a solid co-occurrence network between the cervix, vagina and urethra, in which the vaginal microbiome was the most interactive with the rest of the site in female and was most influenced by the cervical microbiome. This was consistent with previous studies, cervix and vagina have certain similarities in their microbial composition [ 30 , 38 ]. At the same time, we found that Lactobacillus and Gardnerella , the two most common probiotics and pathogenic bacteria in the reproductive tract, have positive correlations in three parts of cervix, vagina and urethra, and these two common bacteria genera in the reproductive tract may have cross-site interactions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we have found a solid co-occurrence network between the cervix, vagina and urethra, in which the vaginal microbiome was the most interactive with the rest of the site in female and was most influenced by the cervical microbiome. This was consistent with previous studies, cervix and vagina have certain similarities in their microbial composition [ 30 , 38 ]. At the same time, we found that Lactobacillus and Gardnerella , the two most common probiotics and pathogenic bacteria in the reproductive tract, have positive correlations in three parts of cervix, vagina and urethra, and these two common bacteria genera in the reproductive tract may have cross-site interactions.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, in addition to the common high-risk types such as HPV16, HPV18 and HPV58 detected, we also found that low-risk types such as HPV44 and HPV81 present in multiple sites with high infection rates, it may have a certain impact on the composition of the microbial community in the female urogenital tract. In one of our previous studies, we found that HPV detected in cervical swabs is high-risk, while low-risk HPV is mainly found in vaginal and rectal swabs, and multiple subtypes of infection are common [ 38 ]. Some studies have found that HPV44 is one of the common types in tumor tissues of cervical cancer patients [ 56 ], frequently detected in human intestines [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have found a solid co-occurrence network between the cervix, vagina and urethra, in which the vaginal microbiome was the most interactive with the rest of the site in female and was most in uenced by the cervical microbiome. This was consistent with previous studies, cervix and vagina have certain similarities in their microbial composition (30,33). At the same time, we found that Lactobacillus and Gardnerella, the two most common probiotics and pathogenic bacteria in the reproductive tract, have positive correlations in three parts of cervix, vagina and urethra, and these two common bacteria genera in the reproductive tract may have cross-site interactions.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the analyzed literature (Table 1), significant differences were observed in the cervicovaginal microbiome between the HPV-positive and HPV-negative women. Generally, a wider variety of bacterial species was observed in the HPV-positive women, primarily due to the abundance of species other than Lactobacillus and a shift towards anaerobic bacteria [31,36,41,111,117,130,133,[135][136][137]139,143]. The majority of the studies indicated that HPV-negative women had a normal cervical microbiota characterized by the abundance of Lactobacillus.…”
Section: Decrease: Hpv+hsil Groupmentioning
confidence: 99%